2013
DOI: 10.1093/cvr/cvt151
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 inhibits angiotensin II-induced hypertensive cardiac remodelling

Abstract: Smad7 plays a protective role in Ang II-induced cardiac remodelling via mechanisms involving the Sp1-TGF-β/Smad-NF-κB-miR-29 regulatory network. Thus, Smad7 may be a novel therapeutic agent for hypertensive cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 37 publications
8
78
0
Order By: Relevance
“…23,24 Given that Smad7 interferes with Smad2/3 activation, cardiac Smad7 overexpression blocked TGF-b1 signaling. 25 Our results indicated a significant increase in TGF-b1 expression and Smad2/3 phosphorylation, as well as decreased Smad7. AA treatment blocked Smad2/3 activation and increased Smad7 expression.…”
Section: Discussionsupporting
confidence: 52%
“…23,24 Given that Smad7 interferes with Smad2/3 activation, cardiac Smad7 overexpression blocked TGF-b1 signaling. 25 Our results indicated a significant increase in TGF-b1 expression and Smad2/3 phosphorylation, as well as decreased Smad7. AA treatment blocked Smad2/3 activation and increased Smad7 expression.…”
Section: Discussionsupporting
confidence: 52%
“…Smad7 is an important inhibitory Smad that suppresses Smad2/3 activation and reduces the fibrotic response [19,20,21,22]. Our results suggest that upregulation of Smad7 may be a key to ameliorating atrial fibrosis with EPL.…”
Section: Resultsmentioning
confidence: 78%
“…Third, knockdown of Smad7 abolished the protective roles of EPL. Consistently, Smad7, a downstream inhibitory Smad in TGF-β 1 signaling, was demonstrated to block phosphorylation and activation of Smad2/3 [21,27,28]. Overexpression of Smad7 inhibited collagen synthesis in cardiac myofibroblasts of adult rats [29].…”
Section: Discussionmentioning
confidence: 97%
“…With inhibition of the renin-angiotensin system, clinical trials demonstrated significant benefit in the prevention of cardiac remodeling and myocardial fibrosis [19,20]. Moreover, Ang II given exogenously to rodents has been shown to result in cellular changes within the myocardium, hypertrophy and eventual fibrosis, similar to that seen in humans [20,21,22,23]. Taken together, this evidence strongly supports a role for Ang II in the development of myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 86%